Mental Health Concept in Islamic Education - Huda, Miftahul; Slamet, Slamet (International Journal of Educatio Elementaria and Psychologia, 2024)
Mental health issues can pose a hindrance to the growth and development of students in the educational process and their pursuit of a future. Support from family, educational institutions, and the community is crucial. Unfortunately, currently, mental health service programs in Islamic educational institutions are not consistent, and there is no systematic management of mental health education based on Islamic principles, resulting in suboptimal early detection of mental health disorders. However, Islam places significant emphasis on human mental health. This article aims to explain the principles of managing mental health education based on Islamic teachings. The research method used is qualitative with a literature review approach. The principles of managing mental health in educational institutions involve both promotive and preventive aspects and engage various stakeholders, including guidance counselors, parents, medical professionals, psychologists, and psychiatrists. These principles encompass efforts to eliminate the stigma surrounding mental health issues, implement sustainable programs, assist staff, students, and teachers in early detection of mental health disorders, foster two-way communication, provide mental health services, and enhance well-being. Additionally, Islamic teachings pay special attention to human mental health by promoting the purification of the soul with sincerity, a moderate approach, setting an example, maintaining obedience, avoiding sinful acts, and drawing closer to Allah.